Lenalidomide Augments Differentiation of Cultured Hair Follicle Derived Melanocyte Stem Cells Into Functional Melanocytes - Kumari, Uma; Pervaiz, Naveed; Kaur, Harjot; Sharma, Himani; Parsad, Davinder; Kumar, Ravinder (Dermatology Practical & Conceptual, 2023)
Introducion: Melanocyte progenitors are embryonically derived from the neural crest and subsequently get localized in hair follicles and epidermis to provide hair and skin pigmentation. These progenitor cells in hair follicles repeatedly proliferate and differentiate to maintain pigmentation. Vitiligo, a pigmentary disorder, is associated with loss of melanocytes. Repigmentation of vitiligo lesions mainly depends upon the proliferation, migration and differentiation of melanocyte stem cells (MelSCs) into functional melanocytes. Current study is designed to check the efficacy of lenalidomide, an imide drug in the differentiation of MelSCs into functional melanocytes.Objectives: Aim of the study is to check the effect of lenalidomide in the proliferation, migration of cultured hair follicle derived melanocyte stem cells and their differentiation into functional melanocytes.Methods: Primary culture of MelSCs was established from whisker hair of C57BL/6 mice. Proliferation and migration of cultured cells were done by MTT assay and boyden’s chamber migration assay, respectively. Effect of lenalidomide on the MelSCs differentiation was checked at gene level by qPCR & protein expression was checked by immunocytochemistry.Results: A significant increase in the migration of MelSCs in comparison to control was also observed. Lenalidomide treatment significantly increased the expression of melanocyte specific genes in cultured MelSCs as compared to control.Conclusion: From the results we concluded that lenalidomide induce the proliferation and migration of MelSCs and accelerate the differentiation of MelSCs into functional melanocytes.